Inverse problem to determine degenerate memory kernels in heat flux with third kind boundary conditions - Pais, E.; Janno, J. (Mathematical Modelling and Analysis, 2006)
An inverse problem to determine degenerate time‐ and space‐dependent relaxation kernels of internal energy and heat flux with third kind boundary conditions by means of temperature measurements is considered. Existence and uniqueness of a solution to the inverse problem are proved.First Published Online: 14 Oct 2010